2018
DOI: 10.1093/nar/gky1124
|View full text |Cite
|
Sign up to set email alerts
|

The European Bioinformatics Institute in 2018: tools, infrastructure and training

Abstract: The European Bioinformatics Institute ( https://www.ebi.ac.uk/ ) archives, curates and analyses life sciences data produced by researchers throughout the world, and makes these data available for re-use globally ( https://www.ebi.ac.uk/ ). Data volumes continue to grow exponentially: total raw storage capacity now exceeds 160 petabytes, and we manage these increasing data flows while maintaining the quality of our services. This year we have improved the efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…We recently demonstrated that CD90 expression is not only restricted to GBM stem-like cells but is also observed in more differentiated GBM cells (primary adherent lines) and in freshly dissociated GBM specimens (Avril et al, 2017a). Using the recent single-cell RNA sequencing datasets from stem-like and no-stem GBM cells and tumor migrating cells (Darmanis et al, 2017; Cook et al, 2018), we confirm herein that CD90 is expressed in tumor cells from the cancer site but also in migrating tumor cells, tumor-associated endothelial cells, and neighboring neuronal cells (Figure 2C). CD90 expression in kidney cancers is currently controversial.…”
Section: Diverse Roles Of Cd90 In Cancerssupporting
confidence: 76%
“…We recently demonstrated that CD90 expression is not only restricted to GBM stem-like cells but is also observed in more differentiated GBM cells (primary adherent lines) and in freshly dissociated GBM specimens (Avril et al, 2017a). Using the recent single-cell RNA sequencing datasets from stem-like and no-stem GBM cells and tumor migrating cells (Darmanis et al, 2017; Cook et al, 2018), we confirm herein that CD90 is expressed in tumor cells from the cancer site but also in migrating tumor cells, tumor-associated endothelial cells, and neighboring neuronal cells (Figure 2C). CD90 expression in kidney cancers is currently controversial.…”
Section: Diverse Roles Of Cd90 In Cancerssupporting
confidence: 76%
“…Such databases have high maintenance costs and mainly play the role of data warehousing. This type of database is represented by the NCBI (Sayers et al ., ), the European Bioinformatics Institute (Cook et al ., ) and the Japanese Nucleic Acid Database (Kodama et al ., ), which are recognized as the three major gene databases. The second category reflects genome databases with particular focus on a group of species.…”
Section: Insect Genome Databasesmentioning
confidence: 99%
“…Accordingly, a considerable fraction of submissions to public databases represents sequence data from large-scale investigations (Kans and Ouellette 2001;Gruenstaeudl and Hartmaring 2019). Data accumulation statistics for nucleotide sequences at ENA corroborate this trend Cook et al 2019). Most sequence databases have, consequently, adopted policies and methods to enable the submission of large-scale sequence datasets.…”
Section: Introductionmentioning
confidence: 77%